THE DESCRIPTION DASH DIET (DIETARY APPROACHES TO STOP HYPERTENSION) MEASURES IN ELDERLY HYPERTENSION IN ISMI MEDIKA CLINIC, KACAGAN VILLAGE, BERBEK DISTRICT, NGANJUK REGENCY - Erni Tri Indarti; Fridelia Andani Putri (Master of Public Health Program Universitas STRADA Indonesia, 2025)
In the elderly with hypertension are very vulnerable so it is recommended to be able to control hypertension well, to prevent more severe diseases. One way to control hypertension is to regulate diet with the DASH diet method. The DASH diet (Dietary Approach to Stop Hypertension) which diet includes emphasizing several food components and nutrients in the form of fruits, vegetables, low-fat dairy products, grains, poultry, fish, and nuts. The purpose of this study was to determine the DASH Diet Action (Dietary Approaches To Stop Hypertension) in the Elderly with Hypertension at the Ismi Medika Clinic, Kacangan Village, Berbek District, Nganjuk Regency. This study used a descriptive design which was carried out on June 1-2, 2024 at the Ismi Medika Clinic, Berbek District, Nganjuk Regency. The population in this study were 20 elderly with hypertension who visited the Ismi Medika Clinic. A sample of 20 respondents using the Total sampling technique. The research variable is the DASH diet action. Data collection using a questionnaire. The results of this study indicate that out of 20 respondents, a small portion, namely 3 respondents (15%) have good actions, a small portion, namely 5 respondents (25%) have sufficient actions, and the majority, namely 12 respondents (60%) have less actions. Based on the results of this study, the majority of respondents' DASH diet actions are in the less category. This can be influenced by age, last education, occupation, whether they have a history of hypertension, how long they have suffered from hypertension. To improve Actions about the DASH diet, namely education about the DASH diet, explaining in detail what the DASH diet is, its principles, and its benefits for health, especially in controlling blood pressure.